Электромагнитные процессы в симметричных индукционных системах с идентичными ферромагнитными тонкостенными экраном и листовой заготовкой - Батыгин, Ю.В.; Гнатов, А.В.; Аргун, Щ.В.; Еремина, Е.Ф. (Електротехніка і електромеханіка, 2012)
The article investigates a symmetric inductor induction system with identical ferromagnetic thin-walled screen and sheet blank. The basic analytical dependences for calculation of the basic electrodynamics characteristics, namely, components of the electromagnetic field excited in the ferromagnetic metal screen and the sheet blank are obtained for the symmetric inductor induction system.